Exploring the Motivation Behind Discrimination and Stigmatization Related to COVID-19: A Social Psychological Discussion Based on the Main Theoretical Explanations - Demirtaş-Madran, H. Andaç (Frontiers in Psychology, 2020)
The novel coronavirus (COVID-19), was first detected in Wuhan province in China during late December 2019 and was designated as being highly infectious. The World Health Organization (WHO) labeled it a “pandemic” on March 11, 2020. Throughout human history, experience has shown that prejudices and viruses spread simultaneously during a viral pandemic. Outgroup members have been associated with various diseases and non-human vectors of diseases. Some epidemics have been named according to various outgroups, just as the novel coronavirus has been referred to by some as the “Wuhan virus” or the “Chinese virus.” Associating a virus with a sociodemographic group builds a false illusionary correlation, which can lead to stigmatization and discrimination. Pandemics can also stimulate violent xenophobic reactions. Besides the obvious harmful consequences for the individuals targeted, pandemic-related discrimination also affects the spread of the virus through its effect on public attitudes towards prevention and restriction, health service procurement, and in the establishment of health-related policies. It is important to first understand the relevant concepts and processes, and also to understand the underlying causes of discrimination in order to fight it. Social psychology offers multidimensional and comprehensive explanations of prejudice and discrimination. This review’s primary aim was to examine the motivations behind COVID-19-related discrimination based on social psychological perspectives. In line with this aim, the review first defines discrimination in detail, plus the related concepts and main social psychological theories on prejudice and discrimination. Then, pandemic-related discrimination in light of past experiences is discussed and explanations put forward for the theoretical perspectives and inferences specific to COVID-19. Finally, recommendations are made in order to prevent and combat discrimination related to infectious diseases.